Work Environment and Compensation as Drivers of Productivity: The Role of Work Discipline as a Mediator - Sujimah, Elis; Musoli (Journal of Management Studies and Development, 2025)
The establishment of a company or government institution is inherently guided by specific organizational objectives that require collective and coordinated efforts. Achieving these objectives depends heavily on the competence of human resources, with employee performance often evaluated through their work productivity. Productive employees demonstrate both efficiency and effectiveness in executing their responsibilities. Work productivity is shaped by various internal and external factors, including the work environment, compensation, motivation, and work discipline. This study aims to examine the mediating role of work discipline in the relationship between the work environment and compensation on employee productivity. A quantitative, explanatory research design was employed. The study population comprised all 90 employees of the Department of Public Works, Housing, and Settlement Areas of Bantul Regency. Given the manageable population size, a total sampling (census) technique was used. Data were collected through a structured, self-administered questionnaire and analyzed using multiple linear regression and mediation analysis via the Sobel test, processed with SPSS version 25. The results indicate that both the work environment and compensation have a positive and significant effect on employee productivity. Additionally, these variables significantly influence work discipline, which itself has a significant positive impact on productivity. The analysis also confirms that work discipline significantly mediates the relationship between both the work environment and compensation and work productivity. The findings support all proposed hypotheses, underscoring the critical role of work discipline in enhancing employee performance through conducive work conditions and appropriate compensation.